Description of Four- and Five-Nucleon Systems by Solving Faddeev-Yakubovsky Equations in Configuration Space - Lazauskas, Rimantas; Carbonell, Jaume (Frontiers in Physics, 2020)
The Faddeev-Yakubovsky equations constitute a rigorous formulation of the quantum mechanical N-body problem in the framework of non-relativistic dynamics. They allow the exact solutions of the Schrödinger equation for bound and scattering states to be obtained. In this review, we will present the general formalism as well as the numerical tools we use to solve Faddeev-Yakubovsky equations in configuration space. We will consider in detail the description of the four- and five-nucleon systems based on modern realistic nuclear Hamiltonians. Recent achievements in this domain will be summarized. Some of the still controversial issues related with the nuclear Hamiltonians as well as the numerical methods traditionally employed to solve few-nucleon problems will be highlighted.